2022
DOI: 10.1001/jamaneurol.2022.0676
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Cortical Tau Positron Emission Tomography Patterns Among Patients With Preclinical Alzheimer Disease

Abstract: IMPORTANCE Characterization of early tau deposition in individuals with preclinical Alzheimer disease (AD) is critical for prevention trials that aim to select individuals at risk for AD and halt the progression of disease.OBJECTIVE To evaluate the prevalence of cortical tau positron emission tomography (PET) heterogeneity in a large cohort of clinically unimpaired older adults with elevated β-amyloid (A+). DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study examined prerandomized tau PET, amyloid PET,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…However, several recent studies also highlighted the heterogeneity of tau spreading patterns [21,[50][51][52]. Consent for publication: Not applicable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, several recent studies also highlighted the heterogeneity of tau spreading patterns [21,[50][51][52]. Consent for publication: Not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the factors in uencing tau tangle replication and propagation inside and outside of MTL in various A/T pro les may offer novel perspectives on comprehending the characteristics of tau pathology and formulating anti-AD clinical trial designs. Additionally, it has been suggested that 28], Klotho-VS heterozygosity(KL-VS het )[29], sex [26,27], and age [19,21,23,25,26] may all be involved to tau increases. Further investigation is needed to determine how they interact with baseline Aβ plaques and tau levels to predict longitudinal tau accumulation in early Braak stages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the more recently introduced technique tau-PET measures more advanced pathological changes as it captures insoluble tau aggregates. 9 Although tau-PET positivity in the neocortex is relatively rare among cognitively unimpaired individuals (~5-10% [10][11][12] ), its presence is strongly associated with worse cross-sectional and longitudinal cognitive outcomes. 13,14 However, large-scale longitudinal studies with amyloid-PET and tau-PET as predictors of clinical progression among cognitively unimpaired individuals are lacking.…”
Section: Introductionmentioning
confidence: 99%